Mortui vivos docent: a modern revival of temporal bone plug harvests - Sagi, Varun; Kosaraju, Nikitha; Moore, Lindsay S.; Mulders, Jip Y.; Solyali, Mehmet; Ma, Xiaojie; Regula, Donald P.; Hooper, Jody E.; Stankovic, Konstantina M. (Frontiers in Neuroscience, 2023)
Human temporal bones (HTBs) are invaluable resources for the study of otologic disorders and for evaluating novel treatment approaches. Given the high costs and technical expertise required to collect and process HTBs, there has been a decline in the number of otopathology laboratories.Our objective is to encourage ongoing study of HTBs by outlining the necessary steps to establish a pipeline for collection and processing of HTBs. In this methods manuscript, we: 1) provide the design of a temporal bone plug sawblade that can be used to collect specimens from autopsy donors; 2) establish that decalcification time can be dramatically reduced from 9 to 3 months if ethylenediaminetetraacetic acid is combined with microwave tissue processing and periodic bone trimming; 3) show that serial sections of relatively-rapidly decalcified HTBs can be successfully immunostained for key inner ear proteins; 4) demonstrate how to drill down a HTB to the otic capsule within a few hours so that subsequent decalcification time can be further reduced to only weeks. We include photographs and videos to facilitate rapid dissemination of the developed methods. Collected HTBs can be used for many purposes, including, but not limited to device testing, imaging studies, education, histopathology, and molecular studies. As new technology develops, it is imperative to continue studying HTBs to further our understanding of the cellular and molecular underpinnings of otologic disorders.